Makna Konotatif Konten Youtube Dr. Richard Lee: Kiki Putra Bongkar Kecurangan UN - Irmaniyatul Khomisah S; Nurus Shobah (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
For humans, language functions as a vital communication tool in life because language is a communication tool for humans or society to interact, and words are useful in conversation. The thing that will be discussed in this research is connotative meaning, namely the meaning of impressions or associations that are usually emotional in nature that are evoked by a word regardless of the boundaries of the dictionary or its basic definition. The aim of this research is to explain the connotative meaning contained in Dr. YouTube. Richard Lee: Kiki Putra Exposes UN Fraud. In analyzing YouTube content, researchers used a qualitative approach and the type of research was descriptive qualitative. The results of this research contain 10 statements of connotative meaning, including the following: 1). Silence, 2). Buying a chair, 3). Overslept Hero, 4). You are handsome, you are a wolf, 5). Government eyes, 6). Shoot at UI, 7). Mummy, 8). Humble, 9). If you attend high school, 10). Dropout.